Body mass index, silent coronary artery disease and the impact of adopting healthy lifestyle and sexual performance on the risk of major adverse cardiovascular events in erectile dysfunction patients. (25th November 2020) - Ioakeimidis, N; Terentes-Printzios, D; Angelis, A; Georgakopoulos, C; Gardikioti, V; Sigala, E; Lazaros, G; Tousoulis, D; Vlachopoulos, C
Abstract: Background: Erectile dysfunction (ED) is associated with a higher prevalence of risk factors such as hypertension and diabetes and it is an independent predictor of major adverse cardiovascular events (MACE). ED is a common problem in men with obesity. Purpose: The aim of this study is to investigate the association of overweight and obesity with asymptomatic coronary artery disease and the impact of lifestyle interventions on MACE risk in men suffering from ED. Methods: A total of 614 patients (55±9 y/o) with ED and without known cardiovascular disease (CVD) underwent dobutamine stress echocardiography (and coronary angiography in patients with positive stress echocardiography for myocardial ischemia) to reveal occult coronary artery disease (CAD). In all patients C-reactive protein (CRP) and total testosterone (TT) were measured at entry. After this evaluation and management of concomitant traditional risk factors they were advised to adopt the recommended strategies for healthy lifestyle and improvement of sexual activity. Results: The whole population was divided into three groups according to body mass index (BMI) at entry (normal: 18–25.5 kg/m 2, n=132; overweight:25.5–29.9 kg/m 2, n=295; and obesity: >29.9kg/m 2, n=187). There were no statistically significant differences in age, blood pressure (BP) level and smoking prevalence between the three groups. Obese ED patients had significantly lower TT and higher CRP compared to overweight and normal BMI patients (overall P<0.001 and P<0.01, respectively). The prevalence of angiographically documented CAD was not different between obese and overweight patients and it was significantly higher compared to that of subjects with normal BMI (13.8% vs 14.5% vs 7.2%, respectively, overall P<0.05). In the whole study population, a total of 43 (7%) MACE occurred during a mean follow-up of 6.7 years after adopting a healthy lifestyle and improvement in sexual life. Interestingly, overweight status at baseline was associated with a higher MACE prevalence and the overall difference between the three BMI groups at entry was statistically significant (Mantel log-rank test: 8.65; P=0.0014) (Figure 1). Furthermore, in a Cox proportional hazard model overweight at entry (3.14, CI: 1.49–7.87, P<0.01), TT level (0.72; CI 0.56–0.97, P<0.01) and the use of phosphodiesterase-5 (PDE-5) inhibitors (0.83; CI 0.67–0.97, P<0.05) were independent predictors of MACE. Conclusion: Overweight and obese ED patients have similar prevalence of asymptomatic CAD, however the overweight profile at baseline appears to have a significantly higher MACE risk compared to obesity at follow-up after adopting a healthy lifestyle and improving sexual life with PDE-5 inhibitors. The paradox finding warrants further investigation. Funding Acknowledgement: Type of funding source: None